Sejarah dan Perkembangan Islamisasi Ilmu Pengetahuan - Susilo, Hadi (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2022)
This article aims to capture the pros and cons of Islamization of knowledge, and to bridge them. The Islamization of knowledge since it surfaced has invited Muslim scientists to discuss it. Muslim scholars who consider the importance of science believe that science is very important to be converted to Islam, because in their view science has been contaminated with Western ideological and philosophical values which are in conflict with Islamic teachings. However, there are still many scientists who do not agree with the Islamization of knowledge